Behavioral Neuroscience 2019
DOI: 10.5772/intechopen.85317
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gut Microbiota on Behavior and Its Disturbances

Abstract: Hippocrates statement that "All disease begins in the gut" continues to be up to date more than 2000 years later. Growing number of scientific reports focus on the important role of intestinal microorganisms for modulation of many systems and human behavior. As a key component of the gut brain, gut microbiota influences the development and maturation of the hypothalamic-pituitary-adrenal axis, affects the development and function of the immune system, regulates the blood-brain barrier, modulates the synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 144 publications
(246 reference statements)
0
8
0
Order By: Relevance
“…Manipulating the intestinal microbiota for the brain benefit is a concept that has become widely acknowledged (Ignatova 2019). Induced modulation of gut microbiota may support the hypothesis that the beneficial effect of MFGM on cognition occurs through the microbiota–gut–brain axis.…”
Section: Nutritional and Health Benefits Of Mfgmmentioning
confidence: 99%
“…Manipulating the intestinal microbiota for the brain benefit is a concept that has become widely acknowledged (Ignatova 2019). Induced modulation of gut microbiota may support the hypothesis that the beneficial effect of MFGM on cognition occurs through the microbiota–gut–brain axis.…”
Section: Nutritional and Health Benefits Of Mfgmmentioning
confidence: 99%
“…The microbiome is important for the immune system, brain and genome. A series of recent studies have demonstrated that the microbiome influences the central nervous system in multiple ways and influences the psychological state of individuals by mediating reactions to stress and anxiety (26)(27)(28)(29)(30). The enteric nervous system (ENS), composed of two layers of approximately 100 million nerve cells that line the digestive tract from the oesophagus to the rectum, is an independent centre for neural processing and integration.…”
Section: Figure 1 Direct and Indirect Mechanisms Of Bacteria Infectin...mentioning
confidence: 99%
“…The brain–gut-microbiota axis has been asserted to play a fundamental role in stress-related mental illnesses and the physiological basis of psychiatry. , Numerous studies have validated the hypothesis that microbiota in the gut affects stress-related behaviors, including depression and anxiety. , Alteration in microbiota-brain–gut signaling is said to have a significant role in gastrointestinal disorders and related psychiatric illness, rendered with an alteration in gut microbiota composition and irregular activity in the HPA (Hypothalamic-Pituitary-Adrenal) axis. , Gut microbiota influences the development and functions of the immune system, control of blood–brain barriers, modulation and recognition of neurotransmitter production, control in neurogenesis, formation of myelination, development and function of the brain. Gut–brain axis disruption is correlated with neuropsychiatric illnesses such as depression, autism spectrum disorders, sleep behavior disorder, rapid eye movement, Alzheimer’s disease, Parkinson’s disease, and other mental disorders . Fecal microbiota profiles of mice from WT (wild type) and KO (Fto knock out) using 16S rRNA amplicon sequencing revealed that the FTO gene (fat mass- and obesity-associated gene) deficiency caused a reduction in anxiety- and depression-like behavior that is linked with the alterations in the microbial ecosystem of the gut .…”
Section: Effect Of Gut–brain Interactions On Mental Healthmentioning
confidence: 99%
“…Gut−brain axis disruption is correlated with neuropsychiatric illnesses such as depression, autism spectrum disorders, sleep behavior disorder, rapid eye movement, Alzheimer's disease, Parkinson's disease, and other mental disorders. 182 Fecal microbiota profiles of mice from WT (wild type) and KO (Fto knock out) using 16S rRNA amplicon sequencing revealed that the FTO gene (fat mass-and obesityassociated gene) deficiency caused a reduction in anxiety-and depression-like behavior that is linked with the alterations in the microbial ecosystem of the gut. 178 Furthermore, given that the microbial transfer can alter stress-induced depressive symptoms, it may be a viable therapy for disorders relating to gut microbial abnormalities.…”
Section: Gutmentioning
confidence: 99%